(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: Translation in the Information Technology (IT) sector plays a pivotal role in facilitating cross-cultural communication, software localization, user experience enhancement, and access to global digital services. With the rapid expansion of digital products and services, the demand for precise, context-aware, and user-friendly translation has grown exponentially. This article explores the multifaceted relationship between translation and information technology, focusing on areas such as software and website localization, technical documentation, machine translation, multilingual user interface design, and international marketing strategies. Additionally, the article analyzes the challenges of terminology consistency, cultural adaptation, and quality assurance in IT translation. It also evaluates the impact of artificial intelligence and neural machine translation on the translation process, highlighting their benefits and limitations. The study concludes that translation is a critical component in making information technologies accessible and effective for a global audience.